Incorporation of Risk Index for Risk Response and Risk Mitigation Strategies of Public-Private Partnership (PPP) Housing Construction Project in Malaysia - Putri Zulaiha, Razi; Mohamad Idris, Ali; Noram Irwan, Ramli (IOP Publishing, 2020)
The present work attempt to derive a risk index that causing performance failures among Public-private partnership (PPP) housing construction project, and to propose a risk response and monitoring strategy based on the risk index obtained. A total of thirty-three (33) respondent involved in the PPP housing construction assessing the risk elements employing the Analytical Hierarchy Process (AHP). Findings reveal that among the risks that were captured for high to extreme risks (0.100 < RI ≤ 0.150) are geologic hazard risk (0.125), and inflation and interest rate risk (0.116) whereas strategy proposed for both of the extreme risks are avoiding the risk and it best to be assigned the risks to the private sector. On contrary, results for moderate risks captured with unreliable value for money (0.066), fluctuation in currency exchange rate (0.058), absence of transparency and accountability during procurement process (0.084), absence of robust and clear agreement (0.077), unforeseen ground condition (0.058) and shortage of technical expertise (0.054) the strategy advocated for the moderate risk is to transfer the risks and shared within both parties i.e. public and private. Eventually, low risks occupied within the risk index of (0.000 < RI ≤ 0.050) are financial incapacity if private partners (0.034), weak state intervention (0.039), persistent land acquisition (0.039), insufficient capacity in procurement and negotiation (0.035), frequent design change (0.039), design over specification (0.023), poor quality workmanship (0.029), absence of specific PPP framework (0.046) and inadequate PPP skills and knowledge leading to poor planning (0.043) all the risks best to accept and retained within the public sectors. Taken together, the development of risk response and risk mitigation plan that emerged from the risk index offered significant contribution which has gain a new understanding that risks with severe or low exposure can be reduced or avoided taking into account its strategic and effective response and mitigation approaches.